PENGARUH KONSENTRASI K2SO4TERHADAP DRUG LOADING ASAM SALISILAT PADA PECTIN EDIBLE FILM - Lilis Kistriyani; Rachman Dwi Nugroho; Morgan Primawan (Faculty of Industrial Technology Universitas Islam Indonesia, 2016)
Waste from orange peel contains pectin that can be utilized as raw material to produce drug delivery system membrane for various types of drugs. Drug loading and release behavior of the membrane can be controlled by adding crosslinker (K2SO4). This research aimed to study the effect of crosslinker composition to the salicylic acid loading as an example of antibiotics. Pectin was dissolved in water, mixed with plasticizers and the variation of K2SO4 solution were 0, 0.1, and 0.2 g / mL at temperature 66°C. The mixture was dried in an oven at temperature 50°C for about 15 hours. The analysis have been done were drug loading, gel sweeling and FTIR. The results show that the more concentration of crosslinker added, the loading of salicylic acid were influenced in range 0.031 – 0.045 g/mL. The parameters estimated by adding K2SO4 crosslinker were gel swelling in range 0,11-0,29 g, whereas FTIR analysis has not significant changein each concentration.